Analisis Status Mutu Air Sungai Gajahwong Segmen Balérejo-Wirokertèn Menggunakan Metode STORET, Indeks Pencemaran, dan Indeks Kualitas Air - Ali Aulia Ghozali; Yoshua; Dewi Eviane; Agnes Dyah Novitasari Lestari (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: Gajahwong River is one of the 3 rivers that pass through the city of Yogyakarta. There are many activities carried out by the local community around the riverbank, such as settlements, industry, which have the potential to affect the water quality of the river. This research was aimed to evaluate the water quality of the Gajahwong River in the Balérejo-Wirokertèn segment and to determine the water quality status using the STORET, Pollution Index and Water Quality Index (IKA). This study used primary data which were examined at 7 sampling points between the Balérejo Bridge to the Wirokertèn Dam. The research was conducted in the dry season, June 2022. The water quality parameters were DO, BOD, phosphate, nitrate, Cu, Ag, pH, temperature, total coliform (CT) and TDS. Based on the results after calculating the status of water quality using these three indices, the Gajahwong River in the study segment has exceeded the Class II quality standard. In addition, it was shown that there were 5 parameters that most dominantly affecting the status of water quality, namely: CT, Cu, Ag, BOD, and phosphate. These five parameters contributed greatly to the decline in the water quality of the Gajahwong River, particularly in the Balérejo-Wirokertèn segment. Generally, river water quality of Gajahwong river in this study is between marginal to heavily polluted.